Enhanced saccadic control in young people with Tourette syndrome despite slowed pro-saccades - Jung, JeYoung; Jackson, Stephen R.; Nam, Kichun; Hollis, Chris; Jackson, Georgina M. (Wiley, 2015)
Tourette syndrome (TS) is a neurodevelopmental disorder characterised by motor and vocal tics. Tics are repetitive and uncontrolled behaviours that have been associated with basal ganglia dysfunction. We investigated saccadic eye movements in a group of young people with TS but without co-morbid ADHD. Participants performed two tasks. One required them to perform only pro-saccade responses (pure pro-saccade task). The other involved shifting, unpredictably, between executing pro- and anti-saccades (mixed saccade task). We show that in the mixing saccade task, the TS group make significantly fewer errors than an age-matched control group, while responding equally fast. By contrast, on the pure pro-saccade task the TS group were shown to be significantly slower to initiate and to complete the saccades (longer movement duration and decreased peak velocity) than controls, while movement amplitude and direction accuracy were not different. These findings demonstrate enhanced shifting ability despite slower reflexive responding in TS and are discussed with respect to a disorder-related adaptation for increased cognitive regulation of behaviour.